Study on Teleological Principle of Methodology in Earth Sciences - Yu N. Golubchikov (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
The article tries to revive the traditions of the teleological dogma that has dropped out of the field of consideration of science. With the establishment of the principle of actualism, the present became the key to the past. All geological processes and phenomena in the past began to be interpreted the same as now. Modern science is based on the fundamental dogma of randomness. The emergence of the universe, life and humanity is deduced as a result of the action of very long, but absolutely blind forces. Until the middle of the nineteenth century geological surveys merged with teleological ones. The neptunist Cuvier believed that «the fossil is the key to the past. The past is characterized by a radical break with the present, perhaps it even proceeded according to another physical laws. This is evidenced by the fossils. Modern processes of decay leave no time for the fossilization of organisms, all the deceased remnants decompose. Fossils could have formed during catastrophically rapid burial with reliable isolation from oxygen. It was impossible to reliably state how many years had passed in that past. The present is the key to the past according to the lawyer Lyell. The past is like the present. It contains an incredible amount of time and years. All processes were going with the same energy as they do now and were not overshadowed by any gigantic disaster. Lyell’s statements entered science under the name of the principle of actualism. He gave a paradigmal form not only to the earth sciences, but to all of science, and formed the basis of the evolutionary doctrine. The fundamental dogma of randomness of both natural and all historical processes is the basis of modern scientific ideology. This randomness has no purpose and cannot have. Nevertheless, paradoxically, it predetermines the evolutionary progress of all things. With the appearance of the anthropic principle the teleologism regains its completeness and direction. Since the entire Universe and the biosphere are attuned to human nature, the more such attunement can be expected from earthly nature. There are opportunities for harmonizing human with natural landscapes for health-improving purposes. Nothing was known about the subtlest adjustment of the Universe for humans, or about the incredible complexity of the biosphere even 50-70 years ago. The universe could be explained by evolution and actualism. The discovered incredible complexity of the world brings religion and science closer together. A catastrophic and probably anti-random picture of the planet’s history is emerging more and more clear. In this light, the power of science is seen again not in confrontation with religion, but in harmonization with it. The role of ideology in modern science is considered.